Connect. Learn. Adapt. Repeat - Practicing adaptive management in complex, conflict-affected environments: barriers and promising practices - Queen, Emily Forsyth (2018)
To shift aid culture toward adaptive management, we can: - Stay humble, empathetic, and build skills in facilitation and listening. - Focus on working with more flexible foundations or individual donors. Or, work for more rigid donors and help make their policies more flexible. - Get clearer about goals and processes while finding ways to be less specific and more committed to local leadership about pathways to get to the goal. - Resist looking for a magic adaptive management tool and instead get clearer about when teams make what kinds of decisions and matching to tools that support that decision-making. - Validate that everyone’s perspective is a form of data and try out simple ways to document how teams learns and changes. - Broaden and ground the idea of expertise – remembering that, especially when working with folx on the margins, people are the only experts on their own life. Practitioners must also examine how dominant patriarchal, white supremacist, colonial ideas have pushed us toward wanting more control, less flexibility, and less space for equitable decision making.

Adaptive Peacebuilding Programming Through Effective Feedback Loops: Promising Practices - Barnard-Webster, Kiely; Jean, Isabella (CDA, 2018)
This case study report was developed by CDA’s part of Peacebuilding Evaluation Consortium collaborative research on the use of feedback loops in support of adaptive programming. Feedback loops are just one element of adaptive programming and are defined and used in different ways by organizations working on social change, peace and development issues. This document includes key findings from our desk review of reports and grey literature, key informant interviews, observations documented during CDA’s advisory and learning engagements with peacebuilding partners as well as the case study on SFCG’s feedback processes in Burundi. The findings are most relevant to program and M&E staff but have implications for senior management and policymakers in light of growing interest in strengthening adaptive management.

Snapshot of Adaptive Management in Peacebuilding Programs - Queen, Emily Forsyth; Baumgardner-Zuzik, Jessica; Hume, Elizabeth; Greenberg, Melanie (Alliance for Peacebuilding, 2018)
The Alliance for Peacebuilding developed the report Snapshot of Adaptive Management in Peacebuilding Programs with support from Humanity United. This report examines how existing organizational programs are designing and learning from adaptive management in a conflict effected and fragile states. It further provides practical recommendations for applying adaptive management to peacebuilding programs based on synthesis … Continue reading "Snapshot of Adaptive Management in Peacebuilding Programs"
Keywords: KEY

Scrambling after Moving Targets: Monitoring & Evaluation Applied to Adaptive Management Approaches in Peacebuilding - Woodrow, Peter; Jean, Isabella (New Directions in Peacebuilding Evaluation, 2019)
In this landmark collection, the voices of pathMakers and innovators in peacebuilding evaluation are assembled to provide new direction for the field.
Keywords: IMPORTANT

Global governance and local peace: accountability and performance in international peacebuilding - Campbell, Susanna (Cambridge University Press, 2018)
Local peacebuilding and global accountability – The country context–Burundi from 1999 to 2014 – Ingos in peacebuilding–globally unaccountable, locally adaptive – International organizations in peacebuilding–globally accountable, locally constrained – Bilateral development donors–accountable for global targets, not local change
OCLC: 1048387754

What can the Thinking and Working Politically community learn from peace and conflict mediation? - Douglas, Alex (From Poverty to Power, 2018)
Wily aid practitioners have long understood the importance of adapting their programs to the political environment, and even use their activities to push politics in a progressive direction. But this magic was spun secretly, hidden behind logframes and results frameworks. Only recently has a range of programs been permitted to escape the dead hand of technocracy. But there was one corner of the development and humanitarian world that never needed to shroud its political ambitions; those of us working on resolving violent conflicts. Donors have always understood our work could never be disembodied from politics. This field included elements of the UN, regional organisations, and NGOs, such as the one I work for: the Centre for Humanitarian Dialogue. With a new focus on development being enabled by a series of ‘deals’ between different actors, it seems timely to examine the strategies used to reach peace agreements and whether they contain broader lessons for TWP/DDD/Adaptive Management.